Analysis of government housing policy in Nigeria - Amdii, I. E. S. (Zaria, Nigeria : Ahmadu Bello University Press, 1993)
The major concern of this work is the analysis of Government housing policy between 1900 and 1993. The approach used in this study is thematic in the sense that the periodization correlated with the various administrations: colonial, post-independence, post - civil war, Shagari and Babangida.
Includes index.
Includes bibliographical references (p. 288-300)
hza 13/02/2019
Loans
Keywords: Housing (policy); Nigeria